The Quality of Machine Translation Assessment On Gender Markers Lingual Units - Hapni Nurliana H.D Hasibuan (Lensa: Kajian Kebahasaan, Kesusastraan, dan Budaya, 2021)
Machine Translation (MT) is one of the most advanced and elaborate research fields within Translation Technology, the quality of MT output has always been a great concern, and MT evaluation is a popular research topic. This research aims to assess the quality translation on the gender markers lingual unit of the Arabic short story "عَبْدُ اللهِ وَالْعُصْفُوْرُ" which is translated to English and Indonesian using Machine Translation. The research was qualitatively-based method. The subject is gender markers lingual unit that taken from the Arabic short story "عَبْدُ اللهِ وَالْعُصْفُوْرُ".  The key instrument of this research is human instrument. Additional instruments used to support this research consisted tables of the lingual units of gender markers and table of rating scales based on Nababans' theory (2012). The research findings showed that this analysis has discovered were 72 lingual units of gender markers in the short story.  Further, the dominant type was personal pronoun. Based on the results, it can be concluded that the google translate translation on the gender markers lingual units have the high quality on the accuracy, acceptance, and readability level.